C-terminal phosphorylation of Hsp70 and Hsp90 regulates alternate binding to co-chaperones CHIP and HOP to determine cellular protein folding/degradation balances - Muller, P; Ruckova, E; Halada, P; Coates, P J; Hrstka, R; Lane, D P; Vojtesek, B (Oncogene, 2013)
Heat shock proteins Hsp90 and Hsp70 facilitate protein folding but can also direct proteins for ubiquitin-mediated degradation. The mechanisms regulating these opposite activities involve Hsp binding to co-chaperones including CHIP and HOP at their C-termini. We demonstrated that the extreme C-termini of Hsp70 and Hsp90 contain phosphorylation sites targeted by kinases including CK1, CK2 and GSK3-β in vitro. The phosphorylation of Hsp90 and Hsp70 prevents binding to CHIP and thus enhances binding to HOP. Highly proliferative cells contain phosphorylated chaperones in complex with HOP and phospho-mimetic and non-phosphorylable Hsp mutant proteins show that phosphorylation is directly associated with increased proliferation rate. We also demonstrate that primary human cancers contain high levels of phosphorylated chaperones and show increased levels of HOP protein and mRNA. These data identify C-terminal phosphorylation of Hsp70 and Hsp90 as a switch for regulating co-chaperone binding and indicate that cancer cells possess an elevated protein folding environment by the concerted action of co-chaperone expression and chaperone modifications. In addition to identifying the pathway responsible for regulating chaperone-mediated protein folding/degradation balances in normal cells, the data provide novel mechanisms to account for the aberrant chaperone activities observed in human cancer cells and have implications for the application of anti-chaperone therapies in cancer treatment.
Keywords: vazba proteinů; Glycogen Synthase Kinase 3 beta; lidé; Glycogen Synthase Kinase 3; Heat-Shock Proteins; HSP70 Heat-Shock Proteins; proteiny teplotního šoku; Protein Binding; Cell Line, Tumor; Female; messenger RNA; RNA, Messenger; Phosphorylation; kinasa glykogensynthasy 3beta; HSP90 Heat-Shock Proteins; ubikvitinligasy; Breast Neoplasms; nádory prsu; Humans; fosforylace; sbalování proteinů; proteiny tepelného šoku HSP70; HEK293 buňky; ženské pohlaví; Protein Folding; proteiny tepelného šoku HSP90; nádorové buněčné linie; kinasa 3 glykogensynthasy; Ubiquitin-Protein Ligases; HEK293 Cells